Dangerous Politics - Annison, H; Harry Annison (2012)
The thesis constitutes a detailed historical reconstruction of the creation, contestation and subsequent amendment of the Imprisonment for Public Protection sentence, the principal ‘dangerous offender’ measure of the Criminal Justice Act 2003. Underpinned by an interpretive political analysis of penal politics, the thesis draws on a detailed analysis of relevant documents and 53 interviews with national level, policy-oriented actors. The thesis explores how actors’ conceptions of ‘risk’ and ‘the public’ interwove with the political beliefs and political traditions relied upon by the relevant actors. It is argued that while there was general recognition of a ‘real problem’ existing in relation to dangerous offenders, the central actors in the creation of the IPP sentence crucially lacked a detailed understanding of the state of the art of risk assessment and management (Kemshall, 2003) and failed to appreciate the systemic risks posed by the IPP sentence. The creation of the IPP sentence, as with its subsequent amendment, is argued to highlight the extreme vulnerability felt by many government actors. The efforts of interest groups and other pressure participants to have their concerns addressed regarding the systemic and human damage subsequently caused by the under-resourcing of the IPP sentence is explored, and the challenge of stridently arguing for substantial change while maintaining ‘insider’ status is discussed. As regards senior courts’ efforts to rein in the IPP sentence, it is argued that the increasingly conservative nature of the judgments demonstrate that the judiciary are not immune from the creep of a ‘precautionary logic’ into British penal politics. Regarding the amendment of the IPP sentence, the Ministry of Justice’s navigation between the twin dangers of a systemic crisis and a political crisis are explored. In conclusion, the IPP story is argued to demonstrate a troubling ‘thoughtlessness’ by many of the key policymakers, revealing what is termed the ‘banality of punitiveness.’ The potential for a reliance on political beliefs and traditions to slip into this thoughtless state, and possible ways of ensuring that such policy issues are engaged with in a more inclusive and expansive manner, are discussed.